Generation means analysis of climbing ability in common bean (Phaseolus vulgaris L.) - Checa Coral, Oscar E.; Ceballos, H.; Blair, Matthew W. (Oxford University Press, 2006)
Climbing common bean (Phaseolus vulgaris L.) genotypes have among the highest yield potential of all accessions found in the species. Genetic improvement of climbing beans would benefit from an understanding of the inheritance of climbing capacity (made up of plant height [PH] and internode length [IL] traits). The objective of this study was to determine the inheritance of climbing capacity traits in 3 crosses made within and between gene pools (Andean × Andean [BRB32 × MAC47], Mesoamerican × Mesoamerican [Tío Canela × G2333], and Mesoamerican × Andean [G2333 × G19839]) using generation means analysis. For each population, we used 6 generations (P1, P2, F1, F2, BC1P1, and BC1P2) that were evaluated at 2 growth stages (40 and 70 days after planting). Results showed the importance of additive compared with the dominant–additive portion of the genetic model. Broad-sense heritabilities for the traits varied from 62.3% to 85.6% for PH and from 66.5% to 83.7% for IL. The generation means analysis and estimates of heritability suggested that the inheritance of PH and IL in climbing beans is relatively simple.